Perspectives on last mile logistics: a sustainable approach - Davila Granda, Mauricio Aarom (2024)
Gradually the urban freight transport to final consumers is gaining relevance worldwide, with a rapid adoption stimulated also by the global health crisis. This also brings to the attention of the world interest regarding its carbon footprint and sustainability; therefore, our objective is to present a review on the diverse ways in which it is proposed to lessen the impact of last mile logistics. For this, a systematic literature review was conducted, using the prism method and the VOS Viewer literature analysis tools. The analysis found a growing interest in the subject, along with proposals in every aspect of the logistics process. The main concern is the actual transportation of the items and the preferred measures to ensure sustainability were the proposals for alternative vehicles, which proved to have the greatest effectiveness in the sustainable development of logistics activities.